Neonatal care in India - Geeta Gathwala (Wolters Kluwer Medknow Publications, 2015)
The last decade has witnessed momentous changes in the Neonatal health scenario in India. Newborn Health care has received unprecedented attention and resources. It is the current focus of Central and state governments and the various funding agencies. And, like never before, there is an opportunity for the champions of newborn health to take their agenda forward . India contributes to one-fifth of global live births and more than a quarter of neonatal deaths. About two-thirds of infant deaths and half of under-five child deaths are during the neonatal period. The neonatal mortality rate has reduced over the years but the decline is at a much slower pace as compared to deaths in the older infant groups. Among neonatal deaths, the rate of decline in early NMR is much lower than that of late NMR. The Millennium Development Goal-4 (MDG-4), which stipulates a two-thirds reduction in under-five deaths by 2015, obviously cannot be achieved without ensuring a substantial reduction in the neonatal mortality rate (NMR). This article reviews the current status of Neonatal Care in India.